CHALLENGES IN THE IMPLEMENTATION OF CLINICAL PATHWAY: A QUALITATIVE STUDY AT PRIVATE HOSPITAL IN JAKARTA - Fushen Fushen; Hery Winoto Tj; Steffe Lie (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2022)
In the universal health coverage era, clinical pathways are generally applied in hospitals for quality and cost control. The utilization of clinical pathways has been widely used and researched. However, limited qualitative research has analyzed the phenomena and challenges for implementing the clinical pathway in Indonesia. This study aims to explore a depth perspective about the challenges in the implementation of the clinical pathway. The results of this study offer alternatives that can complement existing studies and encourage improvement in the use of clinical pathways in Indonesia. This study uses a single case study qualitative approach and descriptive method to describe the challenges of implementing clinical pathways in private hospitals. The challenges encountered were awareness problems, workload imbalances, different perceptions of doctors, and suboptimal hospital management.